1992
DOI: 10.1144/gsl.sp.1992.064.01.06
|View full text |Cite
|
Sign up to set email alerts
|

Foraminiferal production and monsoonal upwelling in the Arabian Sea: evidence from sediment traps

Abstract: Planktonic foraminifera collected in sediment traps in the Arabian Sea during 1986 and 1987 responded to the southern Asian monsoon with changes in productivity, relative abundance of species and isotopic shell chemistry. Most species of foraminifera increased in flux shortly after the advent of the southwest monsoon. G. bulloides increased its production rate by three orders of magnitude. The isotopic chemistry of G. ruber recorded the increase in monsoon upwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 13 publications
4
90
0
Order By: Relevance
“…At most sites, Mg/Ca SSTs are either at or slightly below the observed annual average SST, in accordance with the observation that G. ruber lives year round in the Arabian Sea, but experiences blooms during both monsoon seasons (Curry et al, 1992;Conan and Brummer, 2000;Peeters et al, 2002). The reconstructed west-to-east SST gradient of 2 -4C is consistent with the observed annually averaged and summer SST gradients of 2°C and 4°C, respectively.…”
Section: Sstsupporting
confidence: 87%
See 3 more Smart Citations
“…At most sites, Mg/Ca SSTs are either at or slightly below the observed annual average SST, in accordance with the observation that G. ruber lives year round in the Arabian Sea, but experiences blooms during both monsoon seasons (Curry et al, 1992;Conan and Brummer, 2000;Peeters et al, 2002). The reconstructed west-to-east SST gradient of 2 -4C is consistent with the observed annually averaged and summer SST gradients of 2°C and 4°C, respectively.…”
Section: Sstsupporting
confidence: 87%
“…G. bulloides is only present at this site during the summer upwelling season (e.g. Curry et al, 1992). While G. ruber is present year round, its abundance increases during both the summer and winter monsoon seasons (e.g.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies of sediment traps and core tops have also found that foraminifer δ 13 C is lowest in samples collected during upwelling times or under upwelling centers in many instances (Curry et al, 1992;Kroon and Ganssen, 1989;Sautter Reynolds and Thunell, 1991;Wefer et al, 1983) However, other studies have found a weak relationship between upwelling and foraminifer δ 13 C. For example, Curry et al (1983) found no obvious relationship between δ 13 C and upwelling in near-surface growing species (G. sacculifer and G. ruber) collected in sediment traps from the Panama Basin. Likewise, Curry et al (1992) found that although there was a distinct decrease in foraminifer δ 13 C during peak upwelling in the Arabian Sea, there was not a significant change in foraminifer δ 13 C along a transect from upwelling centers to non-upwelling regions. Finally, Ravelo and Fairbanks (1995) found no clear relationship between foraminifer δ 13 C and depth habitat inferred from shell δ 18 O, despite the large vertical changes in water δ 13 C from the surface mixed layer to thermocline waters.…”
Section: Planktonic Foraminifer δmentioning
confidence: 99%